P1502IS AGE JUST A NUMBER? - HEMODIALYSIS IN OCTOGENARIAN PATIENTS IN A PORTUGUESE CENTRAL HOSPITAL. (6th June 2020) - Alferes, Daniela; Silva, Marinha; Couto, Joana; Ventura, Ana; Sousa, Clemente; Teles, Paulo; Sousa, Sónia; Santos, Maria Clara; Fernandes, João Carlos
Abstract: Background and Aims: The option of a non-dialytic or conservative approach to elderly patients with End-Stage Renal Disease (ESRD) as an alternative to dialysis has a great interest in clinical practice. Among elderly patients with ESRD, the octogenarian ones raise the most difficult decisions with respect to indication and dialysis therapy management, furthermore the evidence about the clinical outcomes is lacking in this group of patient. The main objectives of this study were the analysis the comorbidities and clinical condition of pre-ESRD octogenarians who initiated dialysis and the estimation of the effect of such treatment on this patient group's comorbid status. Method: The authors performed a retrospective and statistical analysis on patients with aged ≥ 80 years who initiated hemodialysis treatment in a Portuguese Central Hospital between 2007 and 2017. A total of 88 patients were included in the study. Results: The mean age of the group was 84±2.8 years; 61.4% were men. Nearly all the patients (97.7%) had one or more comorbid conditions of which the most common were hypertension (86.4%), heart disease (58%) and diabetes (43.2%). In 60.2% of the patients the functional activity was normal (Karnofsky score ≥80). Hemodialysis was initiated in an emergency situation in 58% of the patients and the majority (59.1%) had an arteriovenous fistula as vascular access. In the 2 years previous to dialysis therapy, most patients (54.5%) had at least one hospitalization (min=1; max=4). During the two years of follow-up, the number of hospital admissions decreased ( p =0.034) and only 39.8% of the patients required hospital admission (min=1; max=3) (table 1), with shorter average hospital stay ( p =0.013) (table 2). The main causes of hospitalization in the pre-dialysis period were renal related-diseases, in contrast the admissions were due to non-access related infections and vascular access complications after dialysis had initiated. Most patients died (67%) at the end of follow-up mainly due to non-vascular access infections or sepsis (32.2%). The significant causes of death found by Cox regression were chronic kidney disease secondary to systemic disease, Karnofsky score and hospital stay in the 2-year-dialysis period (table 3). Conclusion: Advanced age in itself should not be used as an excluding factor of dialysis treatment. Comorbidity and performance status are the factors that should exert the greatest influence on such decision. In this sample, the majority of patients had few comorbidities, a good functional activity and they initiated dialysis by an autologous vascular access which may have contributed to the good outcomeS. This study found a decrease in the number of hospitalizations in the dialysis period which can be explained by regular clinical monitoring in every dialysis treatment, preventing or even treating intercurrent illnesses and avoiding hospital admissions.